OP0100 Superior Gains in Bone Mineral Density and Estimated Strength at The Hip for Romosozumab Compared with Teriparatide in Women with Postmenopausal Osteoporosis Transitioning from Bisphosphonate Therapy: Results of The Phase 3 Open-Label Structure Study. (15th July 2016) - Langdahl, B.; Libanati, C.; Crittenden, D.; Bolognese, M.; Brown, J.; Daizadeh, N.; Dokoupilova, E.; Engelke, K.; Finkelstein, J.; Genant, H.; Goemaere, S.; Hyldstrup, L.; et al.
Abstract : Background: In a phase 2 study, treatment with romosozumab significantly increased bone mass in women with low bone mineral density (BMD). Objectives: To report the results of STRUCTURE, a phase 3 study evaluating the effect of romosozumab or teriparatide (TPTD) in women with postmenopausal osteoporosis (PMO) transitioning from bisphosphonate (BP) therapy (NCT01796301 ). Methods: This open-label study enrolled women with PMO who had taken an oral BP for ≥3 years prior to screening and alendronate (70 mg QW or equivalent) in the year prior to screening; had a BMD T-score ≤−2.5 at the total hip (TH), lumbar spine (LS), or femoral neck (FN); and had a history of nonvertebral fracture after age 50 or vertebral fracture. Women were randomized to receive SC romosozumab 210 mg QM or TPTD 20 μg QD for 12 months. The primary endpoint was percent change from baseline in BMD by DXA at the TH through month 12. Secondary endpoints included percent change from baseline at months 6 and 12 in BMD by DXA at the TH, LS, and FN; hip integral and cortical BMD by quantitative computed tomography (QCT); and estimated hip strength by finite element analysis. Results: The 436 women enrolled in the study had a mean age of 72 years and mean TH, LS, and FN T-scores of −2.2, −2.9, and −2.5, respectively. Through 12 months, the mean (95% CI) percent change from baseline in TH BMD by DXA was 2.6% (2.2, 3.0) with romosozumab and −0.6% (−1.0, −0.2) with TPTD ( p <0.0001 between groups). TH BMD changes at months 6 and 12 were significantly larger with romosozumab than with TPTD ( p <0.0001): month 6, 2.3% (1.9, 2.7) vs −0.8% (−1.2, −0.4); month 12, 2.9% (2.5, 3.4) vs −0.5% (−0.9, 0), respectively. Romosozumab also resulted in significantly larger BMD gains at the LS at months 6 and 12 vs TPTD ( p <0.0001): month 6, 7.2% (6.6, 7.8) vs 3.5% (2.9, 4.0); month 12, 9.8% (9.0, 10.5) vs 5.4% (4.7, 6.1), respectively. QCT assessments of the hip demonstrated significantly greater gains in integral and cortical BMD with romosozumab vs TPTD at months 6 and 12 ( p <0.0001). Estimated hip strength gains were also significantly larger with romosozumab at both time points ( p <0.0001) and declined from baseline in TPTD-treated subjects at month 6. The subject incidences of adverse events were generally balanced between treatment groups. Conclusions: In subjects transitioning from BP therapy, romosozumab was well-tolerated and associated with greater BMD gains and improved estimated hip strength compared with TPTD. Acknowledgement: Amgen Inc./UCB Pharma funded Disclosure of Interest: B. Langdahl Grant/research support from: Eli Lilly, Orkla, Consultant for: Amgen Inc., Eli Lilly, Merck, UCB Pharma, C. Libanati Shareholder of: UCB Pharma, Employee of: UCB Pharma, D. Crittenden Shareholder of: Amgen Inc., Employee of: Amgen Inc., M. Bolognese Grant/research support from: Amgen Inc., Lilly, Pfizer, Sanofi, Consultant for: Amgen Inc., J. Brown Grant/research support from: Amgen Inc., Eli Lilly, Consultant for: Amgen Inc., Eli Lilly, Merck, N. Daizadeh Shareholder of: Amgen Inc., Employee of: Amgen Inc., E. Dokoupilova Consultant for: Amgen Inc., K. Engelke Employee of: BioClinica, J. Finkelstein: None declared, H. Genant Consultant for: Amgen Inc., Janssen, Lilly, Merck, Roche, Synarc, S. Goemaere Consultant for: Amgen Inc., MSD, Novartis, L. Hyldstrup Consultant for: Amgen, Denmark; Eli-Lilly, Denmark, E. Jodar-Gimeno Consultant for: Amgen Inc., MSD, T. Keaveny Shareholder of: O.N. Diagnostics, Consultant for: Agnovos, Amgen Inc., O.N. Diagnostics, D. Kendler Grant/research support from: Amgen Inc., Astalis, Astra Zeneca, Eli Lilly, Consultant for: Amgen Inc., Eli Lilly, Merck, Pfizer, P. Lakatos: None declared, J. Maddox Shareholder of: Amgen Inc., Employee of: Amgen Inc., J. Malouf Grant/research support from: Amgen Inc., Lilly España, F. Massari: None declared, J. Molina Grant/research support from: Amgen Inc., M. Ulla: None declared, A. Grauer Shareholder of: Amgen Inc., Employee of: Amgen Inc.